Working conditions of Chagas' disease patients in a large Brazilian city - Maria Elena Guariento; Maria Virgínia Fernandes Camilo; Ana Maria Arruda Camargo
This study evaluated the working conditions of Chagas' disease patients in the city of Campinas, São Paulo, focusing on two-hundred-fifty patients with steady employment and treated at the University Hospital (HC-FCM/Unicamp): 98% were working-age and 77.6% were men. The origin of the patients reflected the migratory process occurring among this population. Most of the patients had limited professional skills, while 63.6% had not finished primary school and 21.6% were illiterate. However, 63.6% were regularly employed under duly processed work contracts. Their jobs were mainly in general services (21.6%) and heavy industry (21.2%). Some 55% of the patients reported a monthly income less than or equal to U$100.00, and 40.4% reported having been fired at least once during the last ten years, in 8.9% of the cases because of a diagnosis of Chagas' disease. Of the patients undergoing pre-hiring physical examinations (57.2%), 9.1% were refused, 92.3% of whom due to positive serology for T. cruzi. Finally, 78.4% reported not belonging to a labor union. The study demonstrated the precarious working conditions and discrimination experienced by workers with Chagas' disease.